The French Musculoskeletal Disorders Surveillance Program: Pays de la Loire network. Issue 7 (5th March 2009) - Ha, C; Roquelaure, Y; Leclerc, A; Touranchet, A; Goldberg, M; Imbernon, E
Abstract : Objectives: An epidemiological surveillance system for work-related musculoskeletal disorders (MSDs) was implemented in 2002 in France's Pays de la Loire region to assess the incidence and prevalence of MSDs in the general and working populations, identify levels of exposure to occupational risk factors and investigate the proportion of cases attributable to work exposure. Methods: The program combines (1) surveillance of sentinel health events in the general population (carpal tunnel syndrome (CTS) was the sentinel event for upper limb MSDs), (2) assessment of the prevalence of the main upper limb MSDs and their risk factors in the workplace based on a network of occupational physicians and (3) registration of the notification of work-related diseases (WRDs). Results: 1168 incident cases of CTS were included over a 3 year period. The estimated incidence of CTS was 1.00 per 1000 person-years in those aged 20–59 years (0.60 in men and 1.40 in women). The incidence rate was higher in employed than unemployed persons in the year of diagnosis (0.6 per 1000 vs 0.3 in men and 1.7 vs 0.8 in women). The occupational physician network noted high prevalence rates: 11% of men and 15% of women had at least one of the six main upper limb clinically-diagnosed MSDs. The WRD survey showed that MSDs represented 65% of notified WRDs. Conclusion: The Pays de la Loire program plays a significant role in informing the authorities and the public about the state of current MSDs. It is planned to extend it to a routine national surveillance program.